Renal sinus lymphangiectasia: An uncommon entity - Divij Agarwal; Pradeep Hatimota; Chandan J. Das (Indian Journal of Urology, 2025)
Renal lymphangiectasia is a benign disorder characterized by cystic dilatation of lymphatic channels in the kidney. It can occur in the perinephric, renal sinus, and intrarenal locations. We describe an uncommon case of renal sinus lymphangiectasia with a characteristic imaging appearance in a 25-year-old female. She presented with loin pain that was managed conservatively.